Microsoft Exchange server 2010 administration instant reference - St. Cyr, Ken (Sybex serious skills, 2010)
Questions about Exchange Server 2010? Flip open this easy-access guide! Have all your questions about Microsoft's new Exchange Server 2010 answered on the spot with this handy reference guide. Designed for easy access with special headings, thumb tabs, easy-to-read lists, and more, this book is the perfect quick resource for those day-to-day issues that come up just when you least expect them. Covers the number one product of its kind, Microsoft Exchange Server 2010 Offers a quick-access reference for your day-to-day administration of Exchange Server 2010 Includes thumb tabs, secondary and tertiary tables of contents, and special heading treatments to provide quick and easy lookup, as well as quick-reference tables, lists, and step-by-step instruction to provide Exchange administrators answers on the spot Keep this helpful, handy guide within easy reach.